Three thousand years of oyster fisheries: a view from Southeast Queensland, Australia - Tam Smith (Frontiers in Environmental Archaeology)
Oysters are an almost ubiquitous presence in coastal archaeological sites globally. Southeast Queensland is no exception, with oysters frequently the dominant taxon in midden deposits. It has been estimated the total number of oysters at Booral Shell Mound in the Great Sandy Strait to be more than 5.9 million individuals. This paper moves beyond just the number of oysters to examine the structure of populations within the deposits at two Southeast Queensland sites, Booral Shell Mound and White Patch 3, from an Applied Historical Ecology approach. In doing so, the nature and sustainability of First Nations marine resource exploitation may be determined. Additionally, environmental factors influencing molluscan population dynamics can be elucidated. Historical accounts provide insights into observed collection practices in the early colonial period, as well as the persistence of First Nations oystering and other marine resource exploitation in the mid-late 19th century in response to participation in the wider economy of early Brisbane. Reasons for the late nineteenth-early Twentieth century collapse of Southeast Queensland oyster populations are examined and attempts to revive the oyster industry reviewed.